2021
DOI: 10.1093/socpro/spab032
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and Religious Discrimination in the Wedding Venue Business: Evidence from Two Field Experiments in Germany and Austria

Abstract: We add to the current debate on ethno-religious discrimination by studying to what extent discrimination in the wedding venue business is based on religious or ethnic grounds. Do the two reinforce each other? Does the explicit mentioning of a non-religious wedding help to reduce ethnic discrimination in a secularized society? We draw on two field experiments in Germany and Austria. We sent 805 valid emails to wedding venues. We randomly varied two traits, the names (Arabic-origin and native-origin) and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…These findings resonate with studies on actual discrimination of Muslim minorities (e.g. Carol et al, 2023;Di Stasio et al, 2019;Koopmans et al, 2019) and a recent survey experiment on the perceived eligibility of medical treatment for foreigners during the pandemic (Haderup Larsen and Schaeffer, 2021). To conclude, how willing people are to help depends on the ethno-religious origin of a neighbour, the duration of stay, and the type of groceries that are ordered (Figure 2).…”
Section: Treatment Effectssupporting
confidence: 85%
See 1 more Smart Citation
“…These findings resonate with studies on actual discrimination of Muslim minorities (e.g. Carol et al, 2023;Di Stasio et al, 2019;Koopmans et al, 2019) and a recent survey experiment on the perceived eligibility of medical treatment for foreigners during the pandemic (Haderup Larsen and Schaeffer, 2021). To conclude, how willing people are to help depends on the ethno-religious origin of a neighbour, the duration of stay, and the type of groceries that are ordered (Figure 2).…”
Section: Treatment Effectssupporting
confidence: 85%
“…One example that could be studied with survey experiments in the future is the role of assimilation cues. Previous research on the discrimination of people with Arabic names revealed that they were not treated differently from people with native names if secularity was mentioned (Carol et al, 2023). Similarly, the consumption of beer could have been interpreted as signal of assimilation in those five countries, particularly for the neighbour with a Muslim name as the consumption of alcohol is less common among Muslim minorities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The above arguments posit that religion positively affects access to self-employment; however, noteworthily, religion can also negatively affect individuals' participation in the labour market. Indeed, authors such as A ısa and Larramona (2021) and Carol et al (2021) argue that religion promotes discrimination in some cases wherein religious considerations are excessively strong. Similarly, Drakopoulou and Gotsis (2007) argue that in contexts wherein the weight of religion is significant, entrepreneurs tend to rely increasingly on religious criteria when making decisions.…”
Section: Religion and Access To Employment In The Literaturementioning
confidence: 99%
“…The above arguments posit that religion positively affects access to self-employment; however, noteworthily, religion can also negatively affect individuals' participation in the labour market. Indeed, authors such as Aísa and Larramona (2021) and Carol et al. (2021) argue that religion promotes discrimination in some cases wherein religious considerations are excessively strong.…”
Section: Religion and Access To Employment In The Literaturementioning
confidence: 99%